Electromechanical Brillouin scattering in integrated planar photonics - Li, Mo (APL photonics, 2019)
The exploitation of Brillouin scattering, the scattering of light by sound, has led to demonstrations of a broad spectrum of novel physical phenomena and device functionalities for practical applications. Compared with optomechanical excitation by optical forces, electromechanical excitation of acoustic waves with transducers on a piezoelectric material features intense acoustic waves sufficient to achieve near-unity scattering efficiency within a compact device footprint, which is essential for practical applications. Recently, it has been demonstrated that gigahertz acoustic waves can be electromechanically excited to scatter guided optical waves in integrated photonic waveguides and cavities, leading to intriguing phenomena such as induced transparency and nonreciprocal mode conversion, and advanced optical functionalities. The new integrated electromechanical Brillouin devices, utilizing state-of-the-art nanofabrication capabilities and piezoelectric thin film materials, succeed guided wave acousto-optics with unprecedented device integration, ultrahigh frequency, and strong light-sound interaction. Here, we experimentally demonstrate large-angle (60°) acousto-optic beam deflection of guided telecom-band light in a planar photonics device with electromechanically excited gigahertz (∼11 GHz) acoustic Lamb waves. The device consists of integrated transducers, waveguides, and lenses, all fabricated on a 330 nm thick suspended aluminum nitride membrane. In contrast, conventional guided-wave acousto-optic devices can only achieve a deflection angle of a few degrees at most. Our work shows the promises of such a new acousto-optic device platform, which may lead to potential applications in on-chip beam steering and routing, optical spectrum analysis, high-frequency acousto-optic modulators, RF or microwave filters and delay lines, as well as nonreciprocal optical devices such as optical isolators.